Vascular Tissue Engineering: Challenges and Requirements for an Ideal Large Scale Blood Vessel - Devillard, Chloé D.; Marquette, Christophe A. (Frontiers in Bioengineering and Biotechnology, 2021)
Since the emergence of regenerative medicine and tissue engineering more than half a century ago, one obstacle has persisted: the in vitro creation of large-scale vascular tissue (>1 cm3) to meet the clinical needs of viable tissue grafts but also for biological research applications. Considerable advancements in biofabrication have been made since Weinberg and Bell, in 1986, created the first blood vessel from collagen, endothelial cells, smooth muscle cells and fibroblasts. The synergistic combination of advances in fabrication methods, availability of cell source, biomaterials formulation and vascular tissue development, promises new strategies for the creation of autologous blood vessels, recapitulating biological functions, structural functions, but also the mechanical functions of a native blood vessel. In this review, the main technological advancements in bio-fabrication are discussed with a particular highlights on 3D bioprinting technologies. The choice of the main biomaterials and cell sources, the use of dynamic maturation systems such as bioreactors and the associated clinical trials will be detailed. The remaining challenges in this complex engineering field will finally be discussed.